Analisis Pengaruh Keberadaan Wisata Hiu Paus Terhadap Peluang Usaha dan Pemanfaatan Lahan - Andika Pratama; Nurul Hudaningsih; Ulfa Turrahmi; Koko Hermanto (UJMC (Unisda Journal of Mathematics and Computer Science), 2025)
The existence of whale shark tourism in the area around Saleh Bay has not been fully utilized optimally by the local community to improve the economy. Therefore, the purpose of this study is to analyze the relationship between the influence of human resource competency development and whale shark tourism village product management on descriptive business opportunities and land use so that it can be a reference for the Labuhan Jambu community. The Labuhan Jambu community is the respondent of this study as a source for obtaining research data. The method used to analyze the relationship is the Structural Equation Modeling (SEM) method with the Lisrel approach. The results of the study indicate that the development of human resource competencies in whale shark tourism villages has a positive but insignificant effect on descriptive business opportunities and a negative but insignificant impact on land use. Meanwhile, the product management of the whale shark tourism village has a positive and significant impact on descriptive business opportunities and land use.